2014
DOI: 10.1007/s11427-014-4703-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional gene regulation by RNA-binding proteins in vascular endothelial dysfunction

Abstract: Endothelial cell dysfunction is a term which implies the dysregulation of normal endothelial cell functions, including impairment of the barrier functions, control of vascular tone, disturbance of proliferative and migratory capacity of endothelial cells, as well as control of leukocyte trafficking. Endothelial dysfunction is an early step in vascular inflammatory diseases such as atherosclerosis, diabetic vascular complications, sepsis-induced or severe virus infection-induced organ injuries. The expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Diabetes also impacts skeletal muscle function causing muscle weakness and atrophy (Andersen et al, 1997;Hernandez-Ochoa & Vanegas, 2015) RBPs are important regulators of cell survival and function, because they have essential roles in fundamental cellular processes such as proliferation, differentiation, and apoptosis (Brinegar & Cooper, 2016;Castello, Fischer, Hentze, & Preiss, 2013;Gerstberger et al, 2014). Dysregulation of RBPs has been observed in a plethora of diseases including cancer (reviewed in Castello et al, 2013;Gerstberger et al, 2014), neurological (reviewed in Cookson, 2017;Donlin-Asp, Rossoll, & Bassell, 2017), and cardiovascular diseases (reviewed in de Bruin, Rabelink, van Zonneveld, & van der Veer, 2017;Nutter et al, 2016;Verma et al, 2016;Xin, Deng, & Fu, 2014). Several RBPs have been associated with the development of diabetes or with diabetic complications (Ben-Haim, Moshitch-Moshkovitz, & Rechavi, 2015;Chu et al, 2008;Gerken et al, 2007;Lyssenko et al, 2008;Rao et al, 2016;Scott et al, 2007;van Hoek et al, 2008;Wood et al, 2016).…”
Section: Rna-binding Proteinsmentioning
confidence: 99%
“…Diabetes also impacts skeletal muscle function causing muscle weakness and atrophy (Andersen et al, 1997;Hernandez-Ochoa & Vanegas, 2015) RBPs are important regulators of cell survival and function, because they have essential roles in fundamental cellular processes such as proliferation, differentiation, and apoptosis (Brinegar & Cooper, 2016;Castello, Fischer, Hentze, & Preiss, 2013;Gerstberger et al, 2014). Dysregulation of RBPs has been observed in a plethora of diseases including cancer (reviewed in Castello et al, 2013;Gerstberger et al, 2014), neurological (reviewed in Cookson, 2017;Donlin-Asp, Rossoll, & Bassell, 2017), and cardiovascular diseases (reviewed in de Bruin, Rabelink, van Zonneveld, & van der Veer, 2017;Nutter et al, 2016;Verma et al, 2016;Xin, Deng, & Fu, 2014). Several RBPs have been associated with the development of diabetes or with diabetic complications (Ben-Haim, Moshitch-Moshkovitz, & Rechavi, 2015;Chu et al, 2008;Gerken et al, 2007;Lyssenko et al, 2008;Rao et al, 2016;Scott et al, 2007;van Hoek et al, 2008;Wood et al, 2016).…”
Section: Rna-binding Proteinsmentioning
confidence: 99%
“…RNA-binding motif (RBM) genes are ubiquitous genes that encode RNA-binding proteins, which are a group of regulatory proteins that interact with RNA ( 7 ). RBM proteins are associated with a number of cellular activities, including alternative splicing and RNA degradation ( 8 10 ). The mutation of RNA-binding motif genes has been associated with cancer development due to their ability to function in the regulation of proteins at a post-transcriptional level ( 11 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation and angiogenesis in endothelial cells are key components in the progress of cardiovascular diseases (Small and Olson, ). RNA‐binding proteins play a crucial role in miRNA‐dependent functions such as endothelial cell proliferation and viability (Xin et al, ). In this study, we showed that FMRP contributes to proliferation and angiogenesis in endothelial cell by regulating miRNA‐181a and its downstream CaM as well as by activating the CaMKII signaling pathway.…”
Section: Discussionmentioning
confidence: 99%